PENINGKATAN PERTUMBUHAN DAN HASIL PADI BERAS MERAH (Oryza nivara) MELALUI PENAMBAHAN PUPUK NANOSILIKA PADA SISTEM ROOFTOP FARMING - Putri, Olivia Damayanti; Sutini, Sutini; Suhardjono, Hadi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
One type of rice that is rich in potential nutritional content is brown rice, but the production of this type of rice is still far behind compared to other types of rice. Therefore, special efforts are needed to support production, one of which is through the use of superior varieties accompanied by the fulfillment of the right nutrients, especially the Si nutrient. This research aims to determine the effect of adding nanosilica on the growth and yield of red rice. This research used a factorial randomized block design consisting of 2 factors, namely variety (consisting of two levels V1 = Pamera, V2 = Pamelen) and nanosilica concentration (consisting of five levels S0: 0 mL L-1 (control); S1: 7, 5 mL L-1; S2: 10 mL L-1; S3: 12.5 mL L-1; S4: 15 mL L-1.). The results of the research concluded that applying nanosilica colloid to the Pamera and Pamelen varieties at a concentration of 15 mL L-1 was able to increase plant length and number of tillers, as well as speeding up the flowering age of red rice. However, giving nanosilica had no effect on harvest age and yield components.